Properties of the structures created by ecosystem engineers on the soil surface of a Colombian savanna - Decaëns, Thibaud; Galvis, JH; Amézquita Collazos, Edgar (International Center for Tropical Agriculture, 2001)
Fourteen types of physical structures produced on the soil surface by ecological engineers were sampled in the Eastern Plains of Colombia. The invertebrates creating these structures were identified. Some physical (aggregate size and stability, and bulk density) and chemical (C, N, and P contents, and pH) properties of the structures were assessed. Three categories were also identified: (1) earthworm casts characterized by high bulk density (1.3-1.4 g/cm3), large aggregates (7-10 mm), high organic C contents (3%-4%), and assimilable nutrients; (2) termite mounds with low bulk density (0.6-0.9 g/cm3), large aggregates (8-9 mm), high organic C contents (3.5%-10%), and assimilable nutrients; and (3) slightly compact (0.4-0.7 g/cm3) and granular (aggregate size <1.5 mm) termite surface channels and ant nests, with low organic C contents (less than 1.5%) and assimilable nutrients. These results underline the diversity of biogenic structures produced by invertebrates on the surface of the studied soil, and suggest the feasibility of a functional classification of engineer organisms that would take into account the different functional attributes reflected by these structures.